Critical Success Factors Enterprise Resource Planning (ERP) Implementation in Higher Education - Adjeng Kartika Rizkiana; Hamzah Ritchi; Zaldy Adrianto (Journal of Accounting Auditing and Business, 2021)
One of the technologies that can optimize the data management system in Higher Education is the Enterprise Resource Planning (ERP) information system. However, in its implementation, failures often occur. This research was conducted to formulate the key factors for the successful implementation of ERP systems in universities. The research method used is descriptive qualitative through case studies on 4 campuses in West Java. The 20 key factors taken are the result of iterations of 32 works of literature in the 2016-2019 timeframe. The results of the study provide an overview of the key success factors that have emerged at each college and university.